Skills policy and the displacement of industrial relations - Keep, E; Lloyd, C; Payne, J (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2008)
'Skills is the most important lever within our control to create wealth and to reduce social deprivation' (Leitch, 2006:2). The above statement taken from the Treasury-sponsored Leitch Review of Skills reflects the central importance that the UK government attaches to skills as the key to both economic performance and social justice. Skills have not only become the main focus of policy intervention but are increasingly being conceived, at least by policy makers, as an alternative to, or replacement for, more traditional industrial relations concerns. This issues paper explores the reasons behind this policy shift and the challenges it presents for the development of a 'joined up' skills strategy.